Making Tracks Toward the Environmental History of Brazil: A personal journey in historical geography - Bell, Stephen (Fronteira: Journal of Social, Technological and Environmental Science, 2014)
This essay offers a brief personal history of engagement with the fields of historical geography and environmental history. Organized in three sections, working from past to present, the first part mainly reflects on research ideas gained while a student. Concern for the history of ideas about Brazilian land use led to interest in the important work of the German geographer Leo Waibel (1888-1951) concerning the tropics, and most especially Brazil. The second part of the essay reports on recent international research on Waibel. Some interamerican intellectual currents from Waibelâ€™s career are explored for the first time, including his prescient preoccupation from 1939 to map â€œthe catastrophic consequencesâ€ of deforestation across the tropical Americas. The work ends by drawing attention to the importance of the unpublished research of the University of California geographer Henry Bruman (1913-2005) on colonization in postwar Brazil. Although currently an obscure figure in Brazil, Bruman viewed himself as one of Waibelâ€™s intellectual successors. Keywords: Environmental History; Historical Geography; Migration; Colonization; Frontier.